A two-photon responsive naphthyl tagged p-hydroxyphenacyl based drug delivery system: uncaging of anti-cancer drug in the phototherapeutic window with real-time monitoring. Issue 69 (28th July 2020) - Singh, Amit Kumar; Kundu, Moumita; Roy, Samrat; Roy, Biswajit; Shah, Sk. Sheriff; Nair, Asha V; Pal, Bipul; Mondal, Mahitosh; Singh, N. D. Pradeep
Abstract : A two-photon responsive drug delivery system having two-photon absorption (TPA) in the phototherapeutic window with a two-photon uncaging cross-section ≥10 GM and exhibiting real-time monitoring of anti-cancer drug release. Abstract : We report a two-photon responsive drug delivery system (DDS), namely, p -hydroxyphenacyl–naphthalene–chlorambucil ( p HP–Naph–Cbl ), having a two-photon absorption (TPA) cross-section of ≥20 GM in the phototherapeutic window (700 nm). Our DDS exhibited both AIE and ESIPT phenomena, which were utilized for the real-time monitoring of anti-cancer drug release.